Literasi Keuangan, Lingkungan Sosial, Kepercayaan, Pendapatan terhadap Niat Penggunaan ShopeePayLater melalui Motivasi Hedonis sebagai Mediasi pada Mahasiswa S1 Universitas Jambi - Yosfian Capriranda Aji; Ratih Kusumastuti; Riski Hernando (Jurnal Riset Akuntansi, 2026)
The advancement of fintech, particularly the Buy Now Pay Later (BNPL) feature, is influencing student consumption patterns, including Shopee PayLater, which is popular for its convenience dan flexibility. This study aims to examine the influence of financial literacy, social environment, trust, dan income on the intention to use Shopee PayLater, with hedonic motivation as a mediating variable. A quantitative method using a survey dan SEM-PLS analysis using WarpPLS 7.0 was applied, based on UTAUT2 dan TPB theories. The results show that social environment dan income significantly influence intention, while financial literacy dan trust do not. Furthermore, financial literacy, social environment, dan income significantly influence hedonic motivation, but trust does not. Hedonic motivation only mediates the influence of social environment dan income on intention, not financial literacy dan trust. The results confirm that social dan economic factors are more dominant in driving BNPL use through emotional aspects dan pleasurable experiences. This study is expected to contribute to theory dan practice, as well as policy recommendations to improve financial literacy dan the wise use of financial services.